Development of an Educational Gamification Strategy to Enhance the Food Safety Practices of Family Farmers in Public Food Markets of Northeast Brazil: A Case Study - Noádia Priscila Araújo Rodrigues; Mirella Silva de Morais; Nísia Carolina Damacena Bezerra; Erik Henrique Morais Pereira; Élcio Antônio Garcia Júnior; Jéssica Bezerra dos Santos Rodrigues; Sônia de Paula Alexandrino de Oliveira; Evandro Leite de Souza (Foods, 2023)
This study aimed to develop an educational gamification strategy to enhance the food safety practices of family farmers in public food markets in a city in Northeastern Brazil (João Pessoa, PB, Brazil). A good manufacturing practices (GMP) checklist was used to verify hygienic-sanitary conditions in the food markets. Educational game tools addressing foodborne diseases and GMP with information about the prevention of foodborne diseases, good food handling practices, and safe food storage were developed. Pre- and post-training assessments were done to evaluate food handlers’ knowledge and food safety practices. Microbiological parameters of food samples were analyzed before and two months after the training. Results indicated unsatisfactory hygiene conditions in the examined food markets. There was a very strong positive correlation between “implementation of GMP” and “production and process controls” (R = 0.95; p ≤ 0.05) and between “production and process controls” and “hygiene habits of handlers” (R = 0.92; p ≤0.05). There was no homogeneity between answers before and after the training for the knowledge of family farmers regarding “prevention of foodborne diseases” and “safe food handling”. There were improvements in the measured microbiological parameters of foods sold by family farmers after the application of the developed educational gamification training. These results showed the developed educational game-based strategy as being effective in raising awareness of hygienic sanitary practices, helping to promote food safety, and reducing risks for the consumers of street foods at family farmers’ markets.